The Effect Of Green Supply Chain Management And Supply Chain Management Performance On Sustainable Performance - Khoerun Nisa Safitri; Asrul Fole (Performa: Media Ilmiah Teknik Industri, 2026)
This research analyzes the influence of Green Supply Chain Management (Green SCM) and Performance Supply Chain Management (Performance SCM) variables on environmental, economic and social dimensions, as well as their impact on sustainable performance. The confirmatory test results show that the construct indicators used are significant for measuring both endogenous and exogenous latent variables. The estimation method applied is maximum likelihood (ML), which searches for optimal parameters to produce the highest covariance. The proposed model meets most of the goodness of fit criteria, although it is not fit according to the chi square criteria, but is considered feasible based on the existing consensus. Hypothesis testing shows that Green SCM has a positive effect on the environment, economy and social. On the other hand, SCM Performance has no significant effect on the economy. Further analysis indicates that 43.5% of the economic variables can be explained by Green SCM and Performance SCM, while the remaining 56.5% is influenced by other factors. These findings emphasize the importance of implementing Green SCM in supporting sustainable performance.